Lifestyle choices and awareness of fundamental rights - Wojciechowski, Bartosz (Teisė, 2023)
This paper deals with the need to recognise the pluralism of the ways of life in modern legal systems, so that each person in a diverse world can find his or her own modus vivendi. Such an approach is especially relevant when discussing the rights of LGBTQ persons, when the relevant practice of the Supreme Administrative Court of Poland (Naczelny Sąd Administracyjny) can become a starting point. The author notes that the proper implementation of rights and tolerance for the pluralism of values, worldviews or ways of life are impossible without the legal awareness of the members of specific minorities, which is formed by the sensitive and pluralistic approach of judges when making judicial decisions.
Keywords: equality; (non)discrimination; identity; legal consciousness; axiological pluralism; human dignity; recognition